2006
DOI: 10.1073/pnas.0604748103
|View full text |Cite|
|
Sign up to set email alerts
|

End-to-end distance distributions and intrachain diffusion constants in unfolded polypeptide chains indicate intramolecular hydrogen bond formation

Abstract: Characterization of the unfolded state is essential for the understanding of the protein folding reaction. We performed time-resolved FRET measurements to gain information on the dimensions and the internal dynamics of unfolded polypeptide chains. Using an approach based on global analysis of data obtained from two different donor–acceptor pairs allowed for the determination of distance distribution functions and diffusion constants between the chromophores. Results on a polypeptide chain consisting of 16 Gly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
335
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(373 citation statements)
references
References 48 publications
(90 reference statements)
34
335
3
Order By: Relevance
“…* This choice ensures that the results from the Gillespie- separated by a sufficiently long stretch of the chain (>ca.10 residues) at room temperature. [85][86][87][88][89][90][91] This corresponds to the characteristic motional time scale…”
Section: Theoretical Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…* This choice ensures that the results from the Gillespie- separated by a sufficiently long stretch of the chain (>ca.10 residues) at room temperature. [85][86][87][88][89][90][91] This corresponds to the characteristic motional time scale…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Although the results vary, the consensus estimate appears to be D tr $ 10 À6 cm 2 s À1 for a pair of sites separated by a sufficiently long stretch of the chain (>ca.10 residues) at room temperature. [85][86][87][88][89][90][91] This corresponds to the characteristic motional time scale s tr ¼ d 2 0 /D tr $ 2 ns. The results of the computations employing the above set of parameters, d 0 , L, and s tr , are presented in Figure 5 (red bars).…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…These forces determine the dimensions of unfolded and disordered proteins and have been suggested to impact processes such as the coupled binding and folding of IDPs, 5 or the rate of protein folding reactions. [6][7][8] However, the dimensions of unfolded proteins and IDPs also depend critically on solution conditions such as ionic strength, 4,9 temperature, 10 osmolytes, 11 or denaturants, 2,[12][13][14] implying that the complex interplay between chain-chain and chainsolvent interactions has to be unraveled before quantitative predictions of the size of unstructured polypeptide chains and their effect on folding or binding will be possible.…”
Section: Introductionmentioning
confidence: 99%
“…Like the Rouse model the end to end distribution of the polymer chain remains Gaussian in SDCRIF as well. Experiments also showed that Gaussian Distributions of end to end distances of proteins are not too bad approximations [11,62]. Any deviations from the Gaussian behavior is negligibly small [63].…”
Section: Solvent Quality Dependent Compacted Rouse With Internalmentioning
confidence: 92%